ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT PENGAMBILAN KEPUTUSAN PADA PEMERINTAH KOTA PAREPARE - Mayasari Asri (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2021)
The purpose of the research is first to find out the suitability of the cash flow report on the Parepare City Government with the Government Accounting Standard Statement (PSAP) No. 3 of 2010, the second to find out how the cash flow report plays in decision making in the Parepare City Government. This study uses qualitative and comparatively descriptive descriptive methods. This research is a qualitative and comparatively descriptive descriptive study. The research method consists of research objects at the Office of the Regional Financial Agency of Parepare From January to March 2019. In this study, we compared the format in Government Accounting Standard Statement No. 3 of 2010 with the format used in Parepare City Government. Explaining the role of cash flow report as a decision-making tool in the Parepare City Government. The results of this study in Parepare City Government show that in the preparation of its cash flow report, the Parepare City government used PSAP Number 3 of 2010 as its guideline using direct methods. In decision making, the Parepare City Government uses cash flow report analysis as a basis for determining policy.